1995
DOI: 10.1002/jpln.19951580514
|View full text |Cite
|
Sign up to set email alerts
|

The concentrations of K, Rb and Cs in spruce needles (Picea abies Karst.) and in the associated soils

Abstract: Zusammenfassung nK elemend comnrfations of K. Rb and Cc were delemined in needles from individual spruce tms as a function of the needle age class. The concentrations am highest in cumnt year's needles and decrease smoothly in older needles, approaching a constant value. Rb and Cs show similar behaviour. whmas that of K differs in so far as its rclative decnasc with lime is less pronounced. Intm-and intersite variation of the needk concentrations 811: largest for Cs and smallest for K. Individual trees show a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The lowest concentration values were observed in wood (collected as sawdust from different sections of tree trunk, and measured at Babchin only). This finding agrees with previous studies for radiocesium (Fogh and Andersson, 2001) and for stable Cs , and suggests that Cs tends to be translocated to a growing part of a tree like K, although accumulation and uptake of Cs and K may differ (Wyttenbach et al, 1995). and further supports the hypothesis that 137 Cs is taken up by biota similarly to stable Cs as already mentioned above.…”
Section: Concentrations In Biological Samplessupporting
confidence: 90%
“…The lowest concentration values were observed in wood (collected as sawdust from different sections of tree trunk, and measured at Babchin only). This finding agrees with previous studies for radiocesium (Fogh and Andersson, 2001) and for stable Cs , and suggests that Cs tends to be translocated to a growing part of a tree like K, although accumulation and uptake of Cs and K may differ (Wyttenbach et al, 1995). and further supports the hypothesis that 137 Cs is taken up by biota similarly to stable Cs as already mentioned above.…”
Section: Concentrations In Biological Samplessupporting
confidence: 90%
“…However, it is possible that plants may discriminate against cesium uptake because of the large atomic number [15]. There are also clear differences between the vertical distributions of 137 Cs and 40 K in soil.…”
Section: Distribution Of 137 Cs Along the Trunks Of Treesmentioning
confidence: 99%
“…However, in the compilation of data made by Reimann et al (2001), spruce biomass and O horizons on the average had considerably higher K/Rb ratios than C horizon soils, in contrast to the situation at Skogaby. Wyttenbach et al (1995a) argued that the highly variable K/Rb ratios of plants, even within a given plant species, indicates that the uptake of Rb ? is to a greater extent controlled by the precise sorption properties of the soil than by fractionation at the solution-plant interface.…”
Section: Sources Of Weathering Loss Of K At Skogabymentioning
confidence: 99%
“…The complexity of the problem was demonstrated in a study on maize roots by Läuchli and Epstein (1970), where shortage of calcium (Ca) induced preferential loss of K, whereas in the presence of Ca, K and Rb showed a similar behaviour. Wyttenbach et al (1995a) concluded that Rb ? and Cs ?…”
Section: Introductionmentioning
confidence: 99%